Evaluasi Sistem Rekrutmen Non-ASN Berbasis Region-Lock di Kelurahan Pungkur Dengan Pendekatan OECD-DAC - Hutama, Ferdian Al Ghifari Ganda; Fauzi, Dzaki Alwan; Ukasyah, Holis; Fatta, Fawwaz Indra; Felisa, Nayla Bunga Safa; Syamila, Nayla Nur (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The limited number of state apparatus at the regional level has encouraged the government to employ non-civil personnel through various recruitment mechanisms. In Pungkur Subdistrict, the implementation of a region-lock–based recruitment system has become the main strategy to meet service needs while reducing local unemployment. However, this policy does not fully align with the principles of human resource governance based on a merit system. This study aims to evaluate the recruitment and placement policy for non-civil personnel in Pungkur Subdistrict using the OECD-DAC framework, which includes relevance, effectiveness, efficiency, impact, and sustainability. This research employs a descriptive qualitative method through in-depth interviews and observations involving informants at policy, implementation, and beneficiary levels. The findings show that the region-lock system has strong social relevance because it prioritizes local residents and increases employment access through easily accessible information distribution mechanisms. The policy’s effectiveness is reflected in the creation of a harmonious work environment, rapid employee adaptation, and strong community acceptance. In terms of efficiency, the recruitment process is simple and low-cost, although it is not yet supported by adequate competency standards. The policy generates positive impacts on reducing unemployment and strengthening social relations, but it has not significantly improved service quality. The sustainability of the policy is relatively stable due to its long-standing application and easy implementation, though it still faces limitations in professionalism, performance evaluation, and capacity development.